Parental Involvement and English Language Achievement: A Survey of English Education Students at a Private University in Indonesia - Nurhasanah Nurhasanah; M. Arbain (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Parental involvement is widely acknowledged as a key factor in student academic success, particularly in second language acquisition. However, its impact at the university level, especially among pre-service English teachers, remains underexplored. This study investigates the relationship between parental involvement and English language achievement among first-year English Education students at Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin (UNISKA). Employing a quantitative survey design, data were collected from 36 purposively selected participants using a structured Likert-scale questionnaire. The instrument measured both the forms and frequency of parental involvement and students’ self-reported performance in English-related subjects. Data were analyzed using descriptive statistics and Pearson Product-Moment Correlation via SPSS 26. Findings indicate that students generally perceive moderate to high levels of parental involvement, especially in providing academic resources, financial support, and attending university-related events. However, involvement in educational decision-making and career discussions was notably low. A significant positive correlation was found between parental involvement and students' academic performance, particularly in aspects such as discipline, assignment completion, and encouragement. Emotional impacts such as increased motivation or reduced anxiety showed more mixed responses. These findings highlight the enduring influence of parental support in higher education and suggest further exploration of its emotional dimensions.